Sistem Kontrak Perdagangan Pada Bursa Berjangka Jakarta (Commidity Exchange) Dalam Perspektif Hukum Islam - Shandra Puspita Dewi; Hamda Sulfinadia; Efrinaldi Efrinaldi (Jurnal Hukum Ekonomi Syariah, 2024)
Futures trading is conducted on the futures exchange, where this exchange trades futures contracts for various commodities. Investing in futures trading is like presenting two sides of a coin, namely the risk of loss and the potential for profit. The research problem in this study is how the mechanism of the trading contract system on the Jakarta Futures Exchange and how the trading contract system on the Jakarta Futures Exchange is viewed from the perspective of Islamic law and the fatwa of MUI number 80 of 2011. This study is a literature review (library research). The results of this study show that an investor in futures trading does not need to deposit an amount equal to the value of the contract being traded but only a small percentage of the contract value. Every investor can sell their contract before it expires. At the opening of the contract, investors are required to deposit a margin. If, during the contract period, the selling or buying position incurs losses exceeding the set margin limit, the investor will receive a margin call from the AB to provide additional margin funds until it meets the requirements of the initial margin amount. According to Islamic law and fatwa MUI Number 80 of 2011, transactions involving physically and cash-settled goods (spot market) in the perspective of Islamic law can be tolerated. Meanwhile, in futures exchanges, the trading system tends to lean towards prohibited transactions such as the presence of gharar, maysir, or agreements executed when transactions do not fulfill the pillars and conditions of agreements in islamic law.